Changes of intestinal microbiota in the giant salamander (Andrias davidianus) during growth based on high-throughput sequencing - Cai, Mingcheng; Deng, Huan; Sun, Hanchang; Si, Wantong; Li, Xiaoying; Hu, Jing; Huang, Mengjun; Fan, Wenqiao (Frontiers in Microbiology, 2023)
Despite an increasing appreciation of importance of host-microbe interaction in healthy growth, information on gut microbiota changes of Chinese giant salamander (Andrias davidianus) during growth is still lacking. Moreover, identification of monitoring indicator based on microbial community structure would be interesting for farming of A. davidianus. This study explored the composition and functional characteristics of gut bacteria in different growth periods, including tadpole stage (ADT), gills internalization stage (ADG), one year age (ADY), two year age (ADE) and three year age (ADS), using high throughput sequencing. Results showed that significant differences were observed in microbial community composition and abundance among different growth groups. The diversity and abundance of intestinal flora gradually reduced from larvae to adult. Overall, the gut microbial communities were mainly composed of Fusobacteriota, Firmicutes, Bacteroidota and Proteobacteria. More specifically, the Cetobacterium genus was the most dominant, followed by Lactobacillus and Candidatus Amphibiichlamydia. Interesting, Candidatus Amphibiichlamydia, a special species related to amphibian diseases, could be a promising indictor for healthy monitoring during A. davidianus growth. These results could be an important reference for future research on the relationship between host and microbiota, and also provided basic data for artificial feeding of A. davidianus.